Penerapan pembelajaran proyek berbasis fenomenologi pada matakuliah perkembangan peserta didik - Krisna Merdekawati (Refleksi Pembelajaran Inovatif, 2020)
Research uses descriptive approach. The research objective was to describe the achievement of learning outcomes at student development course, using phenomenology-based project learning. The study was conducted at the Islamic University of Indonesia Chemistry Education students who took student development course in the 2018/2019 academic year. The instruments used in the study consisted of research implementation instruments and data collection instruments. The instruments for conducting the research included the lesson plan and the assignment sheet. The instrument for data collection consisted of student satisfaction questionnaires, project assessment, cognitive assessment, and self assessment. The research data shows that phenomenology-based project learning has fulfilled the target set by the study program. Students who meet learning outcomes more than 85%. Phenomenology-based project learning needs to be applied to the lectures of the next course or similar courses. However, the right strategy is needed to monitor the projects undertaken by students. Research in experimental design can be done to strengthen the results of this study.